Ascorbic acid, Carotenoids and beta-(β) Caretene Contents in Different Varieties of Chillies (Capsicum annuum L.) of Bangladesh - Islam, SK Nazrul; Khanam, Jolly; Haque, Saiful; Khan, Md Nazrul Islam; Barua, Sagarmay; Thilsted, SH; Hassan, N (Bangladesh Journal of Nutrition, 2010)
Bangladesh Journal of Nutrition Vol.17 2004 p.7-12